Melatonin Attenuates Sepsis-Induced Acute Lung Injury Through Improvement of Epithelial Sodium Channel-Mediated Alveolar Fluid Clearance Via Activation of SIRT1/SGK1/Nedd4-2 Signaling Pathway - Li, Jing; Liu, Longfei; Zhou, Xiaojun; Lu, Xianzhou; Liu, Xianrong; Li, Guojuan; Long, Jianwu (Frontiers in Pharmacology, 2020)
Acute lung injury is characterized by alveolar vascular barrier injury, and protein-rich pulmonary oedema. Alveolar fluid clearance is closely related to the prognosis of patients with acute lung injury. Melatonin has been shown to have a protective effect on multiple organ injury induced by sepsis. In this study we investigated the effect of melatonin on alveolar fluid clearance (AFC) and explored its potential mechanisms in sepsis-induced acute lung injury. The cecal ligation and puncture was adopted to establish mouse sepsis model. Morphological changes of lung tissues with the hematoxylin staining were observed. AFC and lung wet/dry weight ratio were measured to assess pulmonary edema. Inflammatory mediators in bronchoalveolar lavage fluid were analyzed via enzyme-linked immunosorbent assay. NAD+/NADH and SIRT1 activity were measured by colorimetric assay kit. The protein expressions of epithelial sodium channel (ENaC), silent information regulator1 (SIRT1), SGK1 and Nedd4-2 were immunoblotted by western blot in vivo and in vitro. The distribution of α-ENaC and SIRT1 was detected by immunofluorescence. We found that melatonin attenuated sepsis induced lung injury, improved survival rate, enhanced alveolar fluid clearance, improved SIRT1 activity, increased protein expressions of SIRT1 and ENaC, and activated SGK1/Nedd4-2 pathway. Furthermore, SIRT1 inhibitor EX527 counteracted the effects of melatonin on alveolar fluid clearance and ENaC. These results revealed that melatonin enhanced ENaC-mediated AFC via the SIRT1/SGK1/Nedd4-2 signaling pathway. Our study demonstrated that melatonin might provide a novel therapeutic strategy for sepsis-induced acute lung injury.